The Reader's digest children's atlas of the world (Westport, Conn : Reader's Digest Young Families, 1998)
Contains over fifty detailed maps of the world's continents and countries, and includes physical and political facts, population figures, suggested activities, and other information.
Includes index.
Wilson's Junior High School.
Booklist.
The Science Teacher (N.S.T.A.).
8.0
5-8
Keywords: Children's atlases; Atlases; Atlases; Atlases